2021
DOI: 10.1063/5.0039246
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic driving force of transient negative capacitance of ferroelectric capacitors

Abstract: This paper investigates the thermodynamic driving force of transient negative capacitance (NC) in the series circuit of the resistor and ferroelectric capacitor (R-FEC). We find that the widely used Landau-Khalatnikov (L-K) theory, that is, the minimum of the Gibbs free energy, is inapplicable to explain the transient NC. The thermodynamic driving force of the transient NC phenomenon is the minimum of the difference between the elastic Gibbs free energy and the electric polarization work.The appearance of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…This is consistent with the findings of Chang et al [35]. In addition, several studies indicated a close relationship between the transient NC and the negative curvature of the thermodynamic energy distribution [36,37]. Figure 2(d) demonstrates that both AB and CD periods satisfy d 2 U/dP 2 < 0, proving the existence of the unstable portion of the negative curvature of the thermodynamic energy profile.…”
Section: Mechanisms Of Ncsupporting
confidence: 89%
“…This is consistent with the findings of Chang et al [35]. In addition, several studies indicated a close relationship between the transient NC and the negative curvature of the thermodynamic energy distribution [36,37]. Figure 2(d) demonstrates that both AB and CD periods satisfy d 2 U/dP 2 < 0, proving the existence of the unstable portion of the negative curvature of the thermodynamic energy profile.…”
Section: Mechanisms Of Ncsupporting
confidence: 89%
“…[7] Although this transient NC (TNC) effect was initially explained by the Landau-Khalatnikov (L-K) theory, [7,8] some recent studies argued that this phenomenon is not necessarily associated with the stabilization of NC region in the double-well Gibbs free energy landscape. [9][10][11][12][13] This scenario seems more applicable when the electric field (E) is constant, while in the TNC measurement E is a variable. [12] The domain nucleation limited switching (NLS) model based on the Kolmogorov-Avrami-Ishibashi formulism can successfully interpret the experimental findings for conventional ferroelectrics such as BaTiO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13] This scenario seems more applicable when the electric field (E) is constant, while in the TNC measurement E is a variable. [12] The domain nucleation limited switching (NLS) model based on the Kolmogorov-Avrami-Ishibashi formulism can successfully interpret the experimental findings for conventional ferroelectrics such as BaTiO 3 . [11] As for the HfO 2 -based films, the majority of works show that TNC can be modeled by the multidomain time-dependent L-K scenario.…”
Section: Introductionmentioning
confidence: 99%